A study on association of thrombocytopenia with pregnancy induced hypertension - Donimath, Kasturi V.; Sambrani, Annapurna M.; Rathod, Pratik M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertension is common complication of pregnancy and contributes significantly to maternal and perinatal morbidity and mortality. With incidence of 5-7% of all pregnancy. Platelet count is the most simple and economical method of prediction of PIH, way before the derangements in PT, PTT and TT occur. This study sought the importance of platelet count as the most consistent and reliable method in predicting the severity of PIH. The aim and objectives of the study was to correlate severity of PIH with degree of thrombocytopenia and the degree of thrombocytopenia with fetal and maternal outcome. Methods: Prospective observational study was done during November 2014 to June 2015. A total of 100 cases were included in this period that was diagnosed as PIH. Investigations like platelet count, LFT, RFT, PT were done. Observations were tabulated, analyzed and conclusions were drawn. Results: 66% of all the cases had severe preeclampsia and 56% had thrombocytopenia. There was very high significant relationship between the degree of thrombocytopenia with the severity of the PIH (at p <0.001). 12% of the fetuses had IUD, 10% had IUGR, 4% died after birth and 2% had severe birth asphyxia. 5 % of the mothers had DIC, 3 % showing HELLP syndrome, and 1% died. Conclusions: Thrombocytopenia is the most common complications of PIH and at times is life threatening. Therefore, platelet count can be used as an early, simple, and rapid test to assess the severity of pre eclampsia and prevent progression to HELLP syndrome and DIC.